Interaksi Sosial Anak Down Syndrome di Flexi School Banda Aceh - Putri Regina Lestari; Khalida Ayuni; Hijriati Hijriati (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Down syndrome is one of the children with special needs, where the child has an intellectual level that is low or below average. This study aims to find out, provide an overview, and explain about the forms of social interaction carried out by a child with special needs with Down syndrome with teachers and friends in school. This is done in order to provide a true view and picture of the social behavior that appears from children with Down syndrome, where it has not been widely known by educators and the public. This research is a qualitative research with case study method, this research uses purposive sampling technique. This study uses one subject with certain characteristics. Data collection techniques used are: non-participant observation, interviews, questionnaires, and documentation. Data analysis techniques include: (1) data reduction (2) data presentation, and (3) conclusion drawing. The results of data collection conducted from March 2024, found that there are four forms of behavior that appear classified in social behavior and forms of behavior classified as asocial behavior. The intended social behaviors are friendly behavior, sympathetic behavior, cooperative behavior, and competitive behavior. Existing asocial behaviors consist of resistance behavior and attack behavior.